Terras e conflitos: as disputas territoriais entre os povos das Reduções jesuíticas - Santos, Tiara Cristiana Pimentel dos (2025)
This thesis focuses on the contribution of Indigenous peoples to the formation of the territories known as the Jesuit Missions on the eastern side of the Uruguay River, encompassing the historical period between the 16th, 17th, and 18th centuries. Initially, the research explores the ancestral, cosmological, and territorial perceptions of Indigenous Peoples, based on archaeological studies that helped to understand the territories occupied by these ethnic groups, including the Guarani, the Proto-Jê (Kaingang), and the Minuano-Guenoa peoples. It also examines how perceptions of territoriality and customs were transformed through the incorporation of European elements into Indigenous cultures—one such element being livestock, including cattle, horses, and mules—which brought new meanings and perceptions to Indigenous ways of life in the Americas. These elements also contributed to the delimitation of space. The territories traditionally inhabited by these peoples served as the foundation for analyzing the premises of borders already established by them, allowing for an understanding of how symbolic boundaries created by Indigenous groups influenced the formation of borders in the missionary territories. The study then addresses the reductionist context of the first missionary cycle, as well as the arrival of the first missionaries and the discussions and premises that enabled Europeans to enter territories still largely unexplored by them. The territorial formation promoted by Indigenous peoples contributed to the consolidation and understanding of borders, both in the symbolic context—ancestrally structured by Indigenous groups—and in the European understanding of natural borders, demonstrating the influence of Indigenous ancestral knowledge in this process. The research adopts a documentary approach, employing qualitative methodology and historical method, with emphasis on heuristic critique and interpretation, aiming to develop a plausible historical narrative by articulating various historical sources, especially the disputes involving already established peoples during the second cycle of the Missions, which occurred between the 16th and 18th centuries, with the delimitation of missionary territories.